DIAGNOSTIC AND TREATMENT METHODS FOR URINARY TRACT INFECTIONS IN HEMATOLOGICAL PATIENTS - Hubert Sidor; Radosław Krzysztof Binkowski; Rafał Bednarczyk; Natalia Bednarczyk; Agnieszka Kurek; Natalia Krajewska; Aleksandra Lejman; Aleksandra Mazurkiewicz; Monika Wołosik; Szymon Zysiak (International Journal of Innovative Technologies in Social Science, 2026)
Research Objectives: To evaluate diagnostic and therapeutic methods for urinary tract infections (UTIs) in hematological patients, focusing on both conventional antimicrobial therapy and alternative treatment strategies in this immunocompromised population.Methods: Comprehensive literature review of diagnostic approaches including urine culture techniques, pathogen identification, and antimicrobial resistance patterns. Analysis of therapeutic strategies encompassing empirical and targeted antimicrobial therapy, alongside alternative modalities including cranberry supplementation, probiotics, urinary alkalinization, NSAIDs, and immunotherapy.Results: Hematological patients face elevated UTI risk (34.39% prevalence) with predominant pathogens including E. coli (19.99%) and Klebsiella spp. (5.12%), frequently exhibiting multidrug resistance. Rapid microbiological diagnosis with susceptibility testing is critical for preventing progression to urosepsis. Alternative therapies demonstrate prophylactic potential but cannot replace antimicrobial treatment in established infections.Conclusions: Effective UTI management in hematological patients requires rapid diagnostics, aggressive empirical therapy guided by local resistance patterns, and prompt de-escalation following susceptibility results. Alternative approaches serve valuable adjunctive roles but must not delay definitive antimicrobial therapy. Multidisciplinary collaboration and continuous protocol adaptation based on evolving resistance patterns optimize outcomes in this vulnerable population.